A family with partially penetrant multicentric carpotarsal osteolysis due to gonadal mosaicism: First reported case. Issue 8 (14th May 2021) - Närhi, Anu; Fernandes, Andrea; Toiviainen‐Salo, Sanna; Harris, Jessica; McInerney‐Leo, Aideen; Lazarus, Syndia; Avela, Kristiina; Duncan, Emma L.
Abstract: Multicentric carpotarsal osteolysis (MCTO) is an autosomal dominant condition characterized by carpal–tarsal abnormalities; over half of affected individuals also develop renal disease. MCTO is caused by mutations of MAFB ; however, there is no clear phenotype–genotype correlation. We describe the first reported family of variable MCTO phenotype due to mosaicism: the proband had classical skeletal features and renal involvement due to focal segmental glomerulosclerosis (FSGS), and the father had profound renal impairment due to FSGS, necessitating kidney transplantation. Mosaicism was first suspected in this family due to unequal allele ratios in the sequencing chromatograph of the initial blood sample of proband's father and confirmed by sequencing DNA extracted from the father's hair, collected from different bodily parts. This case highlights the need for a high index of clinical suspicion to detect low‐level parental mosaicism, as well as a potential role for MAFB mutation screening in individuals with isolated FSGS.